The impact of macroeconomic variables on crude palm oil price in Malaysia - Mohamad Isa Abd Jalil; Shariff Umar Shariff Abd. Kadir; Suddin Lada; Joehan Joehari William; Ahmad Aizuddin Hamzah (Penerbit Universiti Malaysia Sabah, 2025)
Crude Palm Oil (CPO) has been a cornerstone of Malaysia's economy for decades, serving as one of the nation's most valuable export commodities. The persistent volatility of CPO prices reflects the inherent uncertainty of commodity markets, necessitating informed decision-making and robust risk management strategies. This dynamic environment requires continued research to unravel the complex relationships between crude palm oil prices and key economic variables, ensuring Malaysia’s palm oil industry remains competitive and resilient in a rapidly changing global market. Thus, this study aims to examine the impact of macroeconomic variables on crude palm oil price in Malaysia. The study employs structural vector autoregressive (SVAR) model, spanning the period from 1971 to 2023. The findings suggest that real GDP positively influences CPO prices, though the response was statistically insignificant. Government expenditure showed a delayed positive impact on CPO prices. The CPI's negative and significant relationship with CPO prices underscores the cost-push effects of inflation. Similarly, the delayed negative impact of interest rates on CPO prices emphasizes the need for careful monetary policy adjustments to support agricultural investment and production.